2022
DOI: 10.1097/inf.0000000000003802
|View full text |Cite
|
Sign up to set email alerts
|

Maternal, Infant, and Breast Milk Antibody Response Following COVID-19 Infection in Early Versus Late Gestation

Abstract: Background: Coronavirus disease 2019 [severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)] infection at varying time points during the pregnancy can influence antibody levels after delivery. We aimed to examine SARS-CoV-2 IgG, IgM and IgA receptor binding domain of the spike protein and nucleocapsid protein (N-protein) reactive antibody concentrations in maternal blood, infant blood and breastmilk at birth and 6 weeks after SARS-CoV-2 infection in early versus late gestation. Methods: Mothers with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…A total of 82 studies were finally included ( 4 , 6 , 9 88 ), including three studies published in Chinese ( 25 , 27 , 28 ). They came from 21 countries, with 26 studies from China (31.7%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 82 studies were finally included ( 4 , 6 , 9 88 ), including three studies published in Chinese ( 25 , 27 , 28 ). They came from 21 countries, with 26 studies from China (31.7%).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-nine studies reported results of antibody testing against SARS-CoV-2 in at least 1,279 breast milk samples from mothers with a confirmed diagnosis of COVID-19 ( 9 , 10 , 62 88 ), and the majority of mothers included in these studies had mild disease severity. All 29 studies showed the presence of at least one of the three antibodies, IgA, IgG and IgM, in breast milk.…”
Section: Resultsmentioning
confidence: 99%
“…Such concepts of protection have been reasonably well-established for many coronaviruses, especially in the veterinary field [ 156 ]. In parallel to the latter, breast milk anti-SARS-CoV-2 antibody declines in the first year [ 157 ]. In keeping with past experience from other respiratory virus infections, there is a strong correlation between increased circulating maternal antibody levels, increased quantities of circulating infant antibody levels, and increased breast milk antibody levels [ 157 ].…”
Section: Controversy Regarding Infantsmentioning
confidence: 99%
“…In parallel to the latter, breast milk anti-SARS-CoV-2 antibody declines in the first year [ 157 ]. In keeping with past experience from other respiratory virus infections, there is a strong correlation between increased circulating maternal antibody levels, increased quantities of circulating infant antibody levels, and increased breast milk antibody levels [ 157 ]. The move to protect mothers from serious disease and protect their infants via the latter through vaccination was justified on theoretical grounds early but then corroborated specifically for COVID-19.…”
Section: Controversy Regarding Infantsmentioning
confidence: 99%
“…The study by Szcygiol and colleagues confirms the presence of SARS-CoV-2 IgA and IgG antibodies in the breastmilk of SARS-CoV-2--recovered women and found no relation of the antibody levels and the trimester of infection. The study, although including all three trimesters, does not elaborate on their specific findings in relation to the trimester of infection, and only collected breastmilk samples at one timepoint [ 7 , 8 , 9 ]. Based on the findings of Fich et al and the lack of representation of all three trimesters in the literature, we hypothesize that the timing of infection in naturally immunized mothers could have a possible impact on future SARS-CoV-2 maternal–neonate immunization.…”
Section: Introductionmentioning
confidence: 99%